Characteristics of Fatigue and Restless Leg Syndrome on Dialysis and Non-Dialysis Days among Patients with Chronic Kidney Disease on Maintenance Haemodialysis: Findings from Southern India: A Cross-Sectional Study (International Journal of Environmental Sciences, 2025)
Background: Patients with Chronic kidney disease (CKD) patients on maintenance haemodialysis may have fatigue and restless leg syndrome which may impact their overall quality of life and activities of daily living. We aimed to characterise and compare the fatigue and restless leg syndrome between dialysis and non-dialysis days. Materials and Methods: This cross-sectional study was conducted at two dialysis centres in Puducherry. 112 subjects who fulfilled the eligibility criteria were selected conveniently and the data collected using standardised instruments namely Fatigue Assessment scale and RLS questionnaire by self-report method. Data analysed by SPSS-20 software, using descriptive and inferential statistics.Results: Out of 112 subjects, 79 (70.54%) comprised males and 33(29.46) were females. The average age was 50.12 ± 13.87 years. The prevalence of RLS in the range of 6.25% (11/112) - 9.82% (7/112) and 31 (27.68%), 47 (41.96%) had fatigued in non-dialysis and dialysis days. The mean fatigue score was found to be 23.12 ± 4.56 and 21.5± 3.89 on dialysis and non-dialysis day respectively which was statistically significant at p<0.05, suggesting fatigue was high on dialysis days compare to non-dialysis days. Among the participants, the average RLS score was 9.82 ± 5.13 and 9.35 ± 4.68 on dialysis and non-dialysis day respectively which was not statistically significant at p<0.05, suggesting no difference in RLS experienced by the patients on dialysis days compared to non-dialysis days. Conclusion: RLS and fatigue are prevalent and debilitating symptoms in CKD patients on both dialysis than non-dialysis days. These findings illuminate the necessity for healthcare providers to routinely screen and managing these symptoms, can enhance the overall quality of life for CKD patients.